Side effects of radiotherapy on breast cancer patients in the Department of Radiotherapy, Lagos University Teaching Hospital, Idi-Araba, Lagos, Nigeria - Sowunmi, Anthonia; Onuoha, Peace C; Alabi, Adewumi; Okoro, Uchenna Samuel (Journal of clinical sciences, 2020)
Background: Side effects of radiotherapy (RT) could be temporary or permanent, can be severe, and affect quality of life. An investigation into the side effects of RT on breast cancer patients would help evaluate the incidences and associated risk factors in the low-income countries for patients undergoing RT in order to ensure maximum treatment with very minimal side effects. Objective: To assess the side effects of RT in patients with breast cancer undergoing RT in Lagos University Teaching Hospital. Materials and Methods: This was a descriptive, cross-sectional study. Self-administered questionnaires were distributed to breast cancer patients on RT that have received treatment for at least 2 weeks at the RT Department between March and August 2016. A total of 146 questionnaires were distributed, whereas 139 were completely filled and returned for the evaluation and analysis, given a response rate of 95.2%. Results: The common side effects noticed from the analysis of this research work included skin erythema (87.1%), fatigue (74.1%), telangiectasia (69.1%), pain (89.9%), breast swelling (45.3%), and loss of hair in the armpit and chest area (87.1%), and the less common ones were breast shrinkage (20.1%), lymphedema (41.0%), cardiac complications (30.9%), lung problems (12.9%), sore throat (7.9%), brachial plexopathy (24.5%), and damage to the bones (ribs; 3.6%). Management of the side effects by patients revealed that 30 (21.6%) used analgesics, 28 (20.1%) used steroidal cream, 27 (19.4%) avoided deodorants and antiperspirant, 22 (15.8%) exercised, 15 (10.8%) took antibiotics, 10 (7.2%) took herbs, and 7 (5%) had to stop treatment temporarily for minimum of a week due to severe morbidity. Conclusion: A large percentage of breast cancer patients undergoing RT experience painful side effects (89.9%), of these 87% experience skin erythema, 74% experience fatigue, and 69% experience telangiectasia.
openalex: W3024891548 mag: 3024891548
Keywords: openalex:import

Evaluation of Three-Dimensional Conformal Radiotherapy and Intensity Modulated Radiotherapy Techniques for Left Breast Post-Mastectomy Patients: Our Experience in Nigerian Sovereign Investment Authority-Lagos University Teaching Hospital Cancer Center, South-West Nigeria - Adeneye, Samuel Olaolu; Akpochafor, Michael Onoriode; Adegboyega, Bolanle; Alabi, Adewumi; Adedewe, Nusirat; Joseph, Adedayo; Fatiregun, Omolara; Omojola, Akintayo Daniel; Adebayo, Abe; Oluwadara, Esther (The Journal of Breast Health, 2021)
This study aimed to evaluate the dosimetric properties of treatment plans obtained from three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy techniques (IMRT) plans for left chest wall breast cancer patients.A total of 20 patients with left-sided chest wall radiotherapy were randomly selected with the dose prescriptions: 42 Gy and 45 Gy in 15 and 18 fractions, respectively. Treatment plans were obtained using 3D-CRT and IMRT for each patient. Five to seven beams were used for IMRT, while tangential beams were used for 3D-CRT. Planning target volume, Dnear-max (D2 ), Dnear-min (D98 ), Dmean, Homogeneity and Conformity Indices (HI and CI) were obtained. Similarly, mean doses to organs at risk (OAR), V5, V10, V20, V25 were generated from the dose-volume histogram and compared.IMRT showed a significant improvement in HI compared to 3D-CRT (p<0.0001). Although there was no significant difference in sparing of the left lung between both plans for high-dose volumes (V20: 18.2 vs 30.55, p<0.0001), (V25: 11.17 vs 28.12, p<0.0001). IMRT however showed supremacy to 3D-CRT with high-dose volumes for the heart, including V20 (4.44 vs 10.29, p = 0.02), V25 (2.08 vs 8.94, p = 0.002). 3D-CRT was better than IMRT in low-dose volumes for left lung (V5: 92.23 vs 56.60, p<0.001; V10: 60.98 vs 47.20, p = 0.04) and heart (V5: 57.45 vs 30.39, p = 0.004).IMRT showed better homogeneity and sparing of high-dose volumes to OAR than 3D-CRT. On the other hand, 3D-CRT showed a reduction of low-dose volumes to OARs than IMRT.
openalex: W3176914785 mag: 3176914785
Keywords: openalex:import